Validation of the Complexity INdex in SARComas prognostic signature on formalin-fixed, paraffin-embedded, soft-tissue sarcomas. (31st May 2018) - Le Guellec, S; Lesluyes, T; Sarot, E; Valle, C; Filleron, T; Rochaix, P; Valentin, T; Pérot, G; Coindre, J -M; Chibon, F
Abstract: Background: Prediction of metastatic outcome in sarcomas is challenging for clinical management since they are aggressive and carry a high metastatic risk. A 67-gene expression signature, the Complexity INdex in SARComas (CINSARC), has been identified as a better prognostic factor than the reference pathological grade. Since it cannot be applied easily in standard laboratory practice, we assessed its prognostic value using nanoString on formalin-fixed, paraffin-embedded (FFPE) blocks to evaluate its potential in clinical routine practice and guided therapeutic management. Methods: A code set consisting of 67 probes derived from the 67 genes of the CINSARC signature was built and named NanoCind ® . To compare the performance of RNA-seq and nanoString (NanoCind ® ), we used expressions of various sarcomas ( n = 124, frozen samples) using both techniques and compared predictive values based on CINSARC risk groups and clinical annotations. We also used nanoString on FFPE blocks ( n = 67) and matching frozen and FFPE samples ( n = 45) to compare their level of agreement. Metastasis-free survival and agreement values in classification groups were evaluated. Results: CINSARC strongly predicted metastatic outcome using nanoString on frozen samples (HR = 2.9, 95% CI: 1.23–6.82) with similar risk-group classifications (86%). While more than 50% of FFPE blocks were not analyzable by RNA-seq owing to poor RNA quality, all samples were analyzable with nanoString. When similar (risk-group) classifications were measured with frozen tumors (RNA-seq) compared with FFPE blocks (84% agreement), the CINSARC signature was still a predictive factor of metastatic outcome with nanoString on FFPE samples (HR = 4.43, 95% CI: 1.25–15.72). Conclusion: CINSARC is a material-independent prognostic signature for metastatic outcome in sarcomas and outperforms histological grade. Unlike RNA-seq, nanoString is not influenced by the poor quality of RNA extracted from FFPE blocks. The CINSARC signature can potentially be used in combination with nanoString (NanoCind ® ) in routine clinical practice on FFPE blocks to predict metastatic outcome.